Understanding the Investment Preferences of Women Professionals: A Regional Perspective (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: The study aims to investigate the investment preferences of women professionals based on their financial priorities such as growth, income, long-term profit, balanced element, tax savings, and short-term earnings. It seeks to examine how these priorities influence their allocation of financial resources across various investment options and to understand the underlying behavioural tendencies guiding their financial decisions.Design/Methodology/Approach: This study adopts a quantitative research design, employing a structured questionnaire administered to 100 women professionals across five Taluks in Kerala. Descriptive statistics were used to summarize investment patterns, and reliability analysis using Cronbach’s Alpha was conducted to assess the internal consistency of financial constructs. Furthermore, regression analysis and ANOVA were performed to evaluate the impact and significance of financial priorities on investment preferences. The analytical approach provides empirical evidence on how women professionals strategically balance risk and returns in their investment behavior.Findings/Result: The findings reveal that women professionals prioritize long-term profit, balanced element, and tax savings when making investment decisions. Regression results demonstrate that these factors significantly influence investment behavior, while short-term profit and income exhibit comparatively lower effects. ANOVA results further confirm statistically significant differences in investment preferences based on financial priorities, indicating a preference for stable and tax-efficient investment options. The study highlights a shift among women professionals toward risk-mitigated, long-term wealth creation strategies.Originality/Value: This research contributes to the growing body of literature on gender-based investment behavior by providing empirical insights into how women professionals in Kerala make strategic investment decisions. It underscores the importance of developing tailored financial products and advisory services aligned with women’s unique financial goals and risk preferences. The study offers practical implications for financial institutions and policymakers aiming to enhance financial inclusion and empower women through informed investment planning.Paper Type: Empirical Research Paper.
Keywords: Investment Preferences; Financial Priorities; Long-term Profit; Women Professionals; Tax Savings; Financial Behaviour; Economic Empowerment